JANGKAUAN PELAYANAN SMP NEGERI PADANGAN KABUPATEN BOJONEGORO PROVINSI JAWA TIMUR - Muh Zainudin; Heribertus Soegiyanto; Mohammad Gamal Rindarjono (GeoEco, 2016)
In the region of Bojonegoro regency, the educational facilities related to the Junior Secondary School service level are not distributed evenly so that many Primary School graduates are not accommodated in Junior Secondary Schools. To improve the access and even distribution of the Junior Secondary Schools’ services affordable to all of the population needs to be done through formal education.The objective of this research is to study the coverage of services of State Junior Secondary School 1 of Padangan as a middle educational facility in rural area. This research is expected to answer the question “How is the coverage of services of State Junior Secondary School 1 of Padangan as a middle educational facility in rural area?” This research used the descriptive qualitative method. Its data included primary and secondary data. The results of the research are as follows: the coverage of services of State Junior Secondary School 1 of Padangan as the educational facility in Bojonegoro regency has reached the region of Padangan sub-district and beyond the sub-district. The result of the nearest neighbor analysis shows that the value of the nearest neighbor (T) of Primary Schools is 0.50 meaning that the spread of Primary Schools in Padangan sub-district tends to be clustered because the index of the nearest neighbor (T) is less than 1. Similarly, the spread of Primary Schools in Padangan sub-district tends to be clustered because the index of the nearest neighbor (T) is 0.48. Based on the results of the research, recommendations are proposed as follows: 1) the educational facilities in Padangan sub-district particularly for the level of Junior Secondary Schools need to be improved by adding the number of classes so as to accommodate the exceeding number of Primary School graduates. 2) educational alternatives and new school units in Padangan sub-district should be established as to fulfill the community’s need. 3) The improvement of quality and facilities of Junior Secondary Schools as a whole is an alternative for the spread of the coverage of school services.Keywords: Coverage of Junior Secondary school services, educational facilities, the nearest neighbor analysis, Padangan sub-district, and Bojonegoro regency.